Efektivitas Model Peningkatan Kompetensi Profesional Guru Biologi Berbasis Continuous Professional Development (CPD) di Karesidenan Surakarta - Anif, Sofyan; Zain, Almuntaqo (Universitas Muhammadiyah Surakarta, 2015)
TheÂ IndonesianÂ LawÂ No.Â 14Â YearÂ 2005Â onÂ teacherÂ andÂ lecturerÂ and Government Regulation No 74 Year 2008 on teacher, have mandated the government to carry out certiï¬ cation for teachers of all subjects who have met the requirements. Based on a survey conducted by the Directorate General of Quality Improvement of Teachers and Education PersonnelÂ (PMPTK) in 2009, the certiï¬ cation program has not been able to improve the competence and professionalism of teachers signiï¬ cantly so it has not given positive inï¬ uence on improving the performance of teachers. The purpose of this study is to determine the effectiveness of the model of professional competenceÂ improvementÂ ofÂ biologyÂ teacherÂ basedÂ onÂ initialÂ competenceÂ testÂ in Surakarta.This research uses R & D approach developed by Borg and Gall (2007), which includes six procedures or stages of development: (1) determine the product; (2) conduct a theoretical and empirical study; (3) development planning; (4) the development of early models; (5) validation of the model; and (6) the discovery of the ï¬ nal product. The ï¬ rst up to the fourth stage has been done in previous studies, and this research isÂ theÂ ï¬ fthÂ stageÂ namelyÂ theÂ stageÂ ofÂ modelÂ validationÂ throughÂ limitedÂ experiment withÂ one-groupÂ pretest-PosttestÂ Design.Â WhileÂ theÂ dataÂ analysisÂ usesÂ traditional descriptive quantitative approach.The results of the study on the effectiveness of implementation of the model of increasing BiologyÂ teacherÂ competenceÂ basedÂ onÂ CPDÂ on Â aÂ limitedÂ scaleÂ testÂ showÂ thatÂ the classical absorption of pretest is 27.78%, while the classical absorption of post-test is 72.22%. It means that Biology teacher competence based on CPD has increased in a limited test scale of 44.44%. The results of a statistical analysis of the increase of pre- test and post-test absorption on each competence shows that the greatest increase of percentage in absorption was on the competence: âunderstanding the concepts, laws, and theories of biology and ï¬ exible implementationâ for 38.89%. While the lowest increase of percentage in the absorption occurred on the competence: âconducting action research to increase professionalismâ with only 13.27%.